Conservation - Hambler, Clive (Cambridge University Press, 2004)
Conservation gives an overview of all aspects of this rapidly changing and controversial field. With the decline of species and our encroachment on natural habitats, conservation is increasingly in the public eye. Maintaining the diversity of life on this planet and using our natural resources in a sustainable manner is important to protect the options of future generations. An understanding of conservation biology is essential to debates and action on the environment. As with all books in the Studies in Biology series, Clive Hambler's text will act as an aid to learning and to field work, and can be used as an introductory text and a study aid for examinations.